UPAYA MENINGKATKAN HASIL BELAJAR SEPAK TAKRAW MELALUI PERMAINAN KRAWNIS PADA SISWA KELAS V SDN 01 DEPOK KECAMATAN SIWALAN KABUPATENPEKALONGAN TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This watchfulness aim the authors strive to increase learning outcomes sepak takraw game with a game thataims menerapan Krawnis motion concept Takraw Association football techniques through games to increasestudent movement activity. So as to allay the fears of students and improve learning outcomes Takraw SoccerGame. This research is a classroom action research was conducted in two cycles. Each cycle has four steps:Planning, Execution, Observation, and Reflection. Data sources were students of class V SD Negeri 01 Depokin 2013 amounted to 19 students, consisting of 9 boys and 10 student daughter. Data analysis techniques usedin this study is a qualitative descriptive statistic. Based on the results of research that learning throughapplication modification of the game, can improve learning outcomes in Football Takraw Elementary Schoolfifth grade students 01 Depok. From the results of the analysis occurs very significant improvement from thefirst cycle and second cycle. Learning outcomes in the first cycle in the category is 79% complete and the secondcycle increasing student learning outcomes in the category at 89.5% complete. It can be concluded that learningTakraw Soccer Games Krawnis can improve student learning outcomes Elementary School District 01 DepokPekalongan. From the results of the analysis obtained a significant improvement from the first cycle and secondcycle.